2000
DOI: 10.1128/aem.66.4.1726-1729.2000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acid Adaptation, Product pH, and Heating on Survival of Escherichia coli O157:H7 in Pepperoni

Abstract: The thermotolerance of E. coli O157:H7 cells (strain 380-94) heated in pepperoni is reported. Information on the pattern of thermal inactivation of E. coli O157:H7 in pepperoni was applied in the development of heating processes designed to reduce E. coli O157:H7 numbers therein by 5 log 10 units.The identification of fermented meat as a vehicle of infection for Escherichia coli O157:H7 (4) has led to the development of heat treatments for such products (3,8,10) such that a 5-log 10 -unit reduction in E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 14 publications
4
24
1
1
Order By: Relevance
“…Contrary to this research, in a study conducted by Riordan et al (28) it was detected that acid adaptation did not result in any increase in the survival rate of E. coli O157:H7 in pepperoni, another fermented meat product. Dlamini and Buys (13) claimed that a significant difference did not exist between survival levels of acid-adapted and nontreated E. coli O157:H7 cells in amasi, also a traditional fermented dairy product, but that in commercial amasi the nontreated cells had a higher survival rate.…”
Section: Discussioncontrasting
confidence: 96%
“…Contrary to this research, in a study conducted by Riordan et al (28) it was detected that acid adaptation did not result in any increase in the survival rate of E. coli O157:H7 in pepperoni, another fermented meat product. Dlamini and Buys (13) claimed that a significant difference did not exist between survival levels of acid-adapted and nontreated E. coli O157:H7 cells in amasi, also a traditional fermented dairy product, but that in commercial amasi the nontreated cells had a higher survival rate.…”
Section: Discussioncontrasting
confidence: 96%
“…Other studies have reported variable quality and sensory effects, ranging from unacceptable to improved sensory scores, due to heat treatments at higher temperatures (≥approx. 50 ∘ C) [105,221,275,276]. Combinations of high temperature and reduced treatment times may be regarded as most feasible in industrial production.…”
Section: Postprocessing Treatments Storage Of Dfs At Elevated Tempermentioning
confidence: 99%
“…Combinations of high temperature and reduced treatment times may be regarded as most feasible in industrial production. Optimal treatment regimes are likely to differ between products with different characteristics [102,221,273,274,276].…”
Section: Postprocessing Treatments Storage Of Dfs At Elevated Tempermentioning
confidence: 99%
“…The data sets used for developing the models for VTEC were obtained from the ComBase database (15) or from the literature (13,20,22,(35)(36)(37)(38) or were kindly provided by the Food Safety Centre, University of Tasmania (39,40). Additional data were generated in this work to address data gaps (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%